2003
DOI: 10.1099/jmm.0.05080-0
|View full text |Cite
|
Sign up to set email alerts
|

Outer-membrane-protein subtypes of Haemophilus influenzae isolates from North India

Abstract: Haemophilus influenzae serotype b and non-typable isolates from blood, cerebrospinal fluid, sputum and throat swabs of patients and carriers in North India were analysed by outer-membrane protein (OMP) profiling. OMP analysis could differentiate the samples into 18 different subtypes. The non-typable isolates were more variable than the serotype b samples. OMP subtypes 1-6 were found only among the serotype b isolates and subtypes 7-18 among the non-typable isolates, while subtypes 2 and 8 were exhibited by bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This is the first report of OMP analysis of serotype b and non-typable strains isolated from confirmed clinical cases in Saudi Arabia although international isolates including Indian strains have been investigated previously [13]. NTHi subtyping by outer membrane protein analysis has proved useful for investigating the transmission of H. influenzae and re-infection epidemiology studies with patients over time [15] but we have shown in this study that sub-typing appears less useful for rapid tracking/surveillance of ampicillin-resistant H. influenzae in populations.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This is the first report of OMP analysis of serotype b and non-typable strains isolated from confirmed clinical cases in Saudi Arabia although international isolates including Indian strains have been investigated previously [13]. NTHi subtyping by outer membrane protein analysis has proved useful for investigating the transmission of H. influenzae and re-infection epidemiology studies with patients over time [15] but we have shown in this study that sub-typing appears less useful for rapid tracking/surveillance of ampicillin-resistant H. influenzae in populations.…”
Section: Discussionmentioning
confidence: 96%
“…Outer membrane protein profiling has been shown to be highly discriminatory in bacterial populations and has been used extensively in the investigation of H. influenzae outbreaks [11][12][13]. In our study, we have differentiated the ampicillin-resistant strains of H. influenzae into two major categories by OMP analysis.…”
Section: Discussionmentioning
confidence: 99%